Legacy Collection : Revenge of the Creature / Creature walks among us - Arnold, Jack, 1916-1992.; Sherwood, John, 1903-1959.; Carlson, Richard, 1912-1977.; Adams, Julie, 1926-2019.; Agar, John, 1921-2002.; Universal Studios Home Entertainment (Firm) (Universal City, CA Universal Studios Home Entertainment, 2014)
Members of a scientific expedition to the Amazon discover a gruesome creature that is half-man and half-fish; "Gill Man" is captured and transported from his Amazon home to a Florida marine park aquarium, where he develops a relationship with a female researcher; despite the clear intention of enjoying his watery home deep in the Everglades, the Creature from the Black Lagoon is disturbed by inquisitive doctors who decide that he would be better off if he were able to walk among men.
Revenge of the creature (1955) / written by Martin Berkeley ; directed by Jack Arnold -- The creature walks among us (1956) / written by Arthur A. Ross ; directed by John Sherwood.
Revenge of the creature: John Agar, Lori Nelson, John Bromfield ; The creature walks among us: Jeff Morrow, Rex Reason, Leigh Snowden.
Originally released as motion pictures 1954-1956.
MPAA rating: Not rated.
Closed-captioned.
108896
Keywords: Monsters -- Amazon River -- Drama; Scientists -- Drama; Amazon River; Video recordings; Horror films; Feature films; Fiction films; Video recordings for the hearing impaired; Drama